2015
DOI: 10.3357/amhp.4245.2015
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Core Strengthening Exercises in Helicopter Crewmembers with Low Back Pain

Abstract: Core strengthening exercises were effective in reducing in-flight pain and led to a reduction in pain symptoms and disability over the 12-wk study period as compared to those subjects who maintained their regular exercise regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 0 publications
9
31
0
Order By: Relevance
“…This finding is not supported by Mohler [37], who advocate physical conditioning as a preventive factor for LBP, and corroborates with studies by O'Sullivan, et al [36] and Da Silva, et al [26], suggesting that physical conditioning is not the most important factor in the prevention of LBG, but the use of specific exercises for the muscles of the trunk aiming at the improvement of strength, endurance, flexibility and spine stabilization [5,6,8,26,[33][34][35][36]. Taking into account only the pilots with complaints of back pain, this average recurrent/transient pain rate corresponds to 93%.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This finding is not supported by Mohler [37], who advocate physical conditioning as a preventive factor for LBP, and corroborates with studies by O'Sullivan, et al [36] and Da Silva, et al [26], suggesting that physical conditioning is not the most important factor in the prevention of LBG, but the use of specific exercises for the muscles of the trunk aiming at the improvement of strength, endurance, flexibility and spine stabilization [5,6,8,26,[33][34][35][36]. Taking into account only the pilots with complaints of back pain, this average recurrent/transient pain rate corresponds to 93%.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, when undergoing a specific program addressed to improve strength and endurance of the deep trunk muscles, the LBP severity was significantly reduced in 36% (p<0.001) [26]. In another study was de demonstrated that core strengthening exercises were effective in reducing inflight pain and led to a reduction in symptoms and disability in helicopter aircrew members [5].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge no studies have fully explored the impact of training on the endurance of the lumbar trunk muscles as well as possible improvement of pain and function in helicopter pilots. A study of five US Air force helicopter crew members did not evaluate lumbar trunk endurance but showed reduced inflight pain with no significant change in function (ODI) [13]. A Swiss study showed improvement in lumbar trunk endurance after training among army helicopter pilots without testing pain [12].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies focus on outcomes such as pain or function [13, 14]. Others focus on lumbar trunk muscular endurance [12, 14, 15].…”
Section: Introductionmentioning
confidence: 99%